Evaluation of arterial stiffness in new diagnosed idiopathic pulmonary arterial hypertension patients. (25th November 2020) - Radchenko, G; Zhyvylo, I; Titov, E; Sirenko, Y.U
Abstract: Objective: This study is the first attempt to use cardio-ankle vascular index (CAVI) for the evaluation of systemic arterial stiffness in patients with IPAH. Methods: 112 patients were included in the study: group 1 – 45 patients with new diagnosed IPAH, group 2 – 32 patients with arterial hypertension, control group – 35 healthy persons adjusted by age. Right heart catheterization, ECG, a 6-minute walk test (6 MWT), echocardiography, blood pressure (BP) measurement and ambulatory BP monitoring, pulse wave elastic artery stiffness (PWVe) [segment carotid-femoral arteries] and muscular artery stiffness (PWVm) [segment carotid-radial arteries], CAVI, N-terminal pro-B-type natriuretic peptide (NT-proBNP) level were provided. The Spearman correlation, a linear regression and multivariable binary logistic analysis were performed to indicate the predictors associated with PWV and CAVI. Results: The PWVm and PWVe were the highest in hypertensive patients – 10.3±1.5 and 11.42±1.70 m/s. The control group and IPAH did not have significant differences in aorta BP, but PWVm/PWVe values were significantly (P<0.003/0.008) higher in IPAH patients than in the control group - 8.1±1.9/8.49±1.92 vs 6.63±1.34/7.29±0.87 m/s. The CAVIs on both sides were significantly lower in the healthy subjects (5.91±0.99/5.98±0.87 right/left side). Patients with IPAH did not differ from the arterial hypertension patients by CAVIs in comparison with the control group - 7.40±1.32/7.22±1.32 vs 7.19±0.78/7.2±1.1. PWVe did not correlate with any parameters except uric acid. PWVm correlated with uric acid (r=0.58, P<0.001), NT-proBNP (r=0.33, P=0.03) and male gender (r=0.37, P=0.013) at Spearman analysis, but not at multifactorial linear regression analysis. The CAVI correlated with age and parameters characterized functional capacity (6 MWT distance) and right ventricle function (NT-proBNP, TAPSE) at Spearman analysis and with age and TAPSE at multifactorial linear regression analysis. At binary logistic regression analysis CAVI >8.0 at right or/and left side had a correlation with age, 6MWT distance, TAPSE, but an independent correlation was only with age (β=1.104, P=0.008, CI 1.026–1.189) and TAPSE (β=0.66, P=0.016, CI 0.47–0.93). Conclusion: In spite of equal and at normal range BP level the age adjusted patients with IPAH had significantly stiffer arteries than the healthy persons and they were comparable with the arterial hypertensive patients. Arterial stiffness evaluated by CAVI correlated with age and TAPSE in IPAH patients. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Academy of Medical science of Ukraine